Pelatihan Desain Grafis untuk Meningkatkan Kompetensi Pembelajaran Siswa Praktik Kerja Lapangan di Rideatama - Muhamad Amiza Surya; Sofiansyah Fadli (Lembaga Pengembangan Kinerja Dosen, 2025)
Graphic design training is an important strategy to enhance student learning competencies, particularly for students participating in the Internship Program (PKL) at Rideatama. This study aims to provide foundational understanding and advanced skills in using the Canva application as an effective learning medium. The training was attended by PKL students from SMKN 1 Kopang with an interactive learning method and hands-on practice. The evaluation results showed significant improvement in creativity, the ability to utilize design features, and students' confidence in developing independent works. The majority of participants stated that the training material was relevant to their needs, and the instructor's delivery was easy to understand, as reflected in the average evaluation score of 86.67%. Although there were some suggestions regarding the training duration being too short, overall, the activity successfully enhanced student learning competencies. This training is expected to serve as a competency development model that is beneficial for both the education and professional sectors, providing skills that can be directly applied in the field of graphic design.